Establishing a global learning community for incident-reporting systems. Issue 5 (25th October 2010) - Pham, Julius Cuong; Gianci, Sebastiana; Battles, James; Beard, Paula; Clarke, John R; Coates, Hilary; Donaldson, Liam; Eldridge, Noel; Fletcher, Martin; Goeschel, Christine A; Heitmiller, Eugenie; Hensen, Jörgen; et al.
Abstract : Background: Incident-reporting systems (IRS) collect snapshots of hazards, mistakes and system failures occurring in healthcare. These data repositories are a cornerstone of patient safety improvement. Compared with systems in other high-risk industries, healthcare IRS are fragmented and isolated, and have not established best practices for implementation and utilisation. Discussion: Patient safety experts from eight countries convened in 2008 to establish a global community to advance the science of learning from mistakes. This convenience sample of experts all had experience managing large incident-reporting systems. This article offers guidance through a presentation of expert discussions about methods to identify, analyse and prioritise incidents, mitigate hazards and evaluate risk reduction.